A Conceptual Study of Nadi Vrana w.s.r to Pilonidal Sinus. - Singh, Manpreet; Rankawat, Shweta; Dixit, Mahesh; Meena, Harimohan (International Research Journal of Ayurveda & Yoga, 2023)
Pilonidal sinus is a frequent condition of the natal cleft in the sacrococcygeal area that causes weak hair buildup in the hair follicles and can be chronic or acute. The patient complains of inflammation related symptoms such as uncomfortable swelling, redness, elevated local temperature, or nasal discharge. Prolonged sitting, the existence of a deep birth cleft, obesity, hair irritation, and a family history of disease may all raise the risk of disease. It is connected to Salyajanya Nadi Vrana (pilonidal sinus), a form of Nadi Vrana (sinus) in Ayurveda. Whose etiology is addressed in Nidanasthana and therapeutic aspects in Susrutha Samhita’s Chikitsasthana. Susrutha mentioned the use of Kshara (caustic alkali) and Ksharasutra (Seton) to treat Nadivrana. Despite the fact that Nadivrana is claimed to be Kricchrasadhya (difficult to cure), studies suggest that Ayurvedic therapy helps to lessen recurrence rate. As a result, successful management of this disease is dependent on knowledge of pathophysiology, patient presentation, and treatment aspects. The concept of nadi vrana w.s.r to pilonidal sinus was explained in this article in light of ayurvedic and modern view.